2020
DOI: 10.31234/osf.io/tg7vz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of messaging and gender on intentions to wear a face covering to slow down COVID-19 transmission

Abstract: Now that various countries are or will soon be moving towards relaxing shelter-in-place rules, it is important that people use a face covering, to avoid an exponential resurgence of the spreading of the coronavirus disease (COVID-19). Adherence to this measure will be made explicitly compulsory in many places. However, since it is impossible to control each and every person in a country, it is important to complement governmental laws with behavioral interventions devised to impact people’s behavior beyond the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
269
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(317 citation statements)
references
References 26 publications
44
269
2
2
Order By: Relevance
“…9 The exceptions are working from home and being female, which remain significant predictors. The gender result is consistent with work by Capraro and Barcelo (2020) and Jordan et al (2020) who show that women are more likely to comply with…”
Section: Resultssupporting
confidence: 87%
“…9 The exceptions are working from home and being female, which remain significant predictors. The gender result is consistent with work by Capraro and Barcelo (2020) and Jordan et al (2020) who show that women are more likely to comply with…”
Section: Resultssupporting
confidence: 87%
“…This is in line with evidence in the literature showing that women are usually risk averse and take more precautions than men [59,60]. A recent study has shown, for example, that women more than men intended to wear a face mask during the Covid-19 pandemic and that men believe it is shameful to wear a face covering [61]. However, while this effect was seen in Study 2, it did not appear in Study 1, which featured a more balanced group of participants in terms of gender and age.…”
Section: Plos Onesupporting
confidence: 87%
“…However, while this effect was seen in Study 2, it did not appear in Study 1, which featured a more balanced group of participants in terms of gender and age. It seems, though, that young men (who were the majority of male participants in Study 2) may feel that needing any measure to protect them from coronavirus is a sign of weakness (see [61] for a similar effect).…”
Section: Plos Onementioning
confidence: 99%
“…The first one is methodological: we develop an experimental design aimed at measuring pandemic relevant actual behaviors. To this end, compared to previous works, we consider a different dependent measure: instead of focusing directly on behaviors such as practicing physical distancing (Everett et al, 2020;Jordan et al, 2020) or wearing a face covering (Capraro & Barcelo, 2020), which are clearly hard to measure in reality, we focus on reading panels containing detailed and official information about the coronavirus. This measure is incentivized, not with money, of course, but with time.…”
Section: Introductionmentioning
confidence: 99%